Estimasi Penentuan Harga Perkiraan Sendiri Menggunakan Use Case Point Untuk Pengembangan Perangkat Lunak Skala Kecil Menengah Dengan Model Agile - Juliyono, Aris; Sutanto, Teguh; Sholiq, Sholiq (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Each application of the procurement of goods / services required the manufacture of Self-Estimated price derived from the approximate (estimated) price of a job (goods / services) to be held. This above is in accordance with Indonesian Presidential Regulation No. 70 Year 2012 on Procurement of Goods / Services, Article 66 digits (5) points a. But what is happening now in the procurement of many software companies individuals or businesses, government officials and developers of software that performs supply and demand for software procurement, had difficulty in making the report HPS. So it can be deduced to solve the problems occurred is needed to set the benchmark in the determination Self-Estimated Price (HPS) method Use Case Point in software development projects by activity agile models. model testing is done using 5 software development project data gets deviation between the estimated level of HPS with the actual cost by 10%, which indicate that the models estimated in this research has a good degree of accuracy.